Dėl i̲ ir u̲ atvirumo pietų žemaičių raseiniškių tarmėje - Atkočaitytė, Daiva (Kalbotyra, 1997)
Lithuanian dialectologists hold that i̲, u̲ in the South Žemaitian dialect of Raseiniai are more open than i, u in Standard Lithuanian, but more closed than ẹ, ọ in North Žemaitian dialects. The experimental analysis has proved that there are two sounds: a more closed i and a more open i similar to the North Žemaitian ẹ; but considerably shorter. Their opposition is only possible in the endings. In the stem their openness depends upon their position, i. e. they are pronounced more openly before a hard consonant and in the acute stressed diphthongs i+l, m, n, r. The distribution of u must be similar.Thus, besides the open i̲, there is a more closed i in the vowel system of the Raseiniai dialect. They may contrast in the endings as phonemes, but in the stem there occur more open or more closed allophones.